Central arterial characteristics of gout patients with chronic kidney diseases. (14th July 2015) - Celik, Gulperi; Yilmaz, Sema; Kebapcilar, Levent; Gundogdu, Ali
Abstract: Background: The aim of this study was to investigate the relationship between central blood pressure, arterial stiffness parameters and renal function parameters in gout patients with chronic kidney disease (CKD) and without CKD. Methods: The study enrolled 48 gout patients and 32 control subjects. Central blood pressure, arterial stiffness parameters and renal function parameters in gout patients were investigated. The vascular measurements were performed with an arteriograph. Results: Of the gout patients, 40.1% had CKD. The 24‐h pulse pressure (PP) ( P  <   0.001), central systolic blood pressure (SBP) ( P  <   0.001), central diastolic blood pressure (DBP) ( P  <   0.001), cardiac output (CO) ( P  <   0.001) and peripheral resistance ( P  =   0.004) were significantly higher in the all patients with gout compared to healthy control subjects. Moreover, when the gout patients with and without CKD were compared, the gout patients with CKD had higher 24‐h PP ( P  =   0.009), 24‐h augmentation index standardized to a heart rate of 75 beats per min (AIx@75) ( P  <   0.023), daytime PP ( P  =   0.001), daytime AIx@75 ( P  =   0.027), and nighttime PP ( P  =   0.035) than the gout patients without CKD. Conclusions: In our study, gout patients with CKD had worse and more emphasized evidence of arterial stiffness than gout patients without CKD. Further investigations with large sample sizes are needed to evaluate the effect of CKD on the arterial stiffness of gout patients.